Sanitizing activity of silver nanoparticles synthesized with natural products on dairy industry surfaces - de Sousa, Maura Marinete; Guimarães, Milena Lima; Tadielo, Leonardo Ereno [UNESP]; Nascimento, Bruna Walleska Campos; Rosa, Danillo Sales; de Oliveira, Helinando Pequeno; Bersot, Luciano Dos Santos; Peixoto, Rodolfo de Moraes; da Costa, Mateus Matiuzzi (FapUNIFESP (SciELO), 2024)
Surface contamination by pathogenic and deteriorating microorganisms is a constant concern in the food industry. Therefore, in this study we evaluated the antimicrobial activity of silver nanoparticles (AgNPs), produced using the essential oil of Lippia origanoides Kunth and ethanolic extract of Hymenaea martiana Hayne, against bacteria used in milk processing. For this, AgNPs were synthesized and their antimicrobial activity was evaluated for minimum inhibitory and bactericidal concentrations, time-kill, interference on the biofilm, and application on the surfaces of different materials. AgNPs showed bacteriostatic and bactericidal activity against Staphylococcus aureus (ATCC 25923), Staphylococcus aureus (ATCC 33591), Escherichia coli (ATCC 25922), Salmonella enterica subsp. enterica serovar Choleraesuis (ATCC 10708), Listeria monocytogenes, Escherichia coli, Salmonella spp.,andPseudomonas aeruginosa,and interfered with biofilm formation more than with consolidated biofilms. A 1hour period was sufficient to reduce the bacterial cells, whereas a Minimum Duration for Killing (MDK) of 99% was reached after approximately 30 min. AgNPs were effective against bacteria attached to stainless steel and polyethylene, but ineffective on tile surfaces. Thus, owing to the growing microbial resistance and the need to develop new products based on the concepts of green chemistry, these AgNPs are presented as a new possibility for cleaning processes in the food industry.
Atividade saneante de nanopartículas de prata sintetizadas com produtos naturais sobre superfícies da indústria de laticínio
Keywords: antibacterial; green synthesis; Hymenaea martiana Hayne; Lippia origanoides Kunth; nanotechnology